Monitoramentos de Panthera onca deve incluir estudos de longo prazo e abordagens genéticas. e2322487 - Fabio Angeoletto; Felipe Alencar da Silva Nogueira; Jeater Waldemar Maciel Correa Santos; Alesson Pires Maciel Guirra (Terr@ Plural, 2023)
Jaguars (Panthera onca Linnaeus, 1758) are predators at the top of food chains, and their occurrence is a good environmental indicator. The study of jaguars, including their behavior, ecology, and conservation, has attracted significant attention from the scientific community. We carried out a scientometric analysis on studies of jaguar biology using camera traps in the Cerrado and Pantanal biomes. Our analysis revealed that conflicts between farmers and ranchers have an important impact on the ecology of the feline movement. We found two important gaps: a scarcity of studies with a genetic approach to the biology of jaguars, which include the ecology of the species movement in the Cerrado and Pantanal biomes. Furthermore, in most studies, jaguars were monitored for short periods, which limits the quality of the data obtained